RESEARCH ON LAYOUT OF LARGE VIBRATING SCREEN SIDE PANEL STIFFENERS BASED ON TOPOLOGY OPTIMIZATION - WANG ChunHua; ZHAO DongHui (Jixie qiangdu)
In order to optimize the layout of the large vibrating screen side panel stiffeners,Topology optimization design was applied in structural design of the side panel stiffeners. The topology optimization model of side panel stiffeners which were based on the goal of maximizing the lateral stiffness of side panel stiffeners was established. According to the pseudo density distribution of the topology optimization,the stiffeners would be rewired. The modal analysis and the harmonic response analysis were done for the panels before and after optimization. Compared with the original side panel structure,the new side panel’s dynamic stress was reduced by 56. 5%,Vibration displacement was reduced by 55. 3%. In addition,the first natural frequency was improved by 72. 03%,the natural frequency was far from working frequency effectively.